Educación virtual y estrés en estudiantes de la carrera de Psicopedagogía de la UNACH - Guaranga Vega, Evelyn Esthefania (2022)
Guaranga Vega, E and Inguillay, A (2022) VIRTUAL EDUCATION AND STRESS IN UNACH PSYCHOPEDAGOGY STUDENTS. (Thesis). Universidad Nacional de Chimborazo. Riobamba, Ecuador. The objective of this work was to determine the level of stress generated by virtual education in students of 1st, the 2nd, 3rd, and 4th semesters of the Psychopedagogy career of the Universidad Nacional de Chimborazo, due to the state of exception declared by the pandemic of Covid-19 where measures are proposed to avoid the massive contagion, opting for virtual education, with limited knowledge, teachers and students had to adapt to this new mode of study that for various factors has caused stressful situations. Regarding the methodology, the research project has a quantitative approach, non- experimental design, descriptive level or scope, primary objectives, and cross-sectional type of study. The population was the students of the Psychopedagogy career, and the sample was non-probabilistic and intentional 146 students, where 83% were women and 17% were men. The results show that no student presents chronic stress, 11% are located in episodic acute stress, and 66% of the surveyed students present acute stress, being the remaining 23% those who do not present stress at any level, reaching the conclusion that more than half of the students have been affected by the change from face-to-face to virtual modality, endangering the equality of educational opportunities. Finally, to establish the analysis of the levels of stress produced by virtual education was carried out through the interpretation of the data collected by means of a questionnaire-type instrument containing questions previously elaborated by the authors of the research work on the characteristics of satisfaction with virtual education and stress according to the needs to be known in the research.